2006
DOI: 10.1103/physrevb.74.024523
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium phase transition in fully frustrated Josephson junction arrays: A short-time dynamic approach

Abstract: The nonequilibrium phase transition of two-dimensional fully frustrated Josephson junction arrays driven by external currents is studied in the framework of the short-time dynamic scaling approach. Within the resistively shunted junction dynamics, besides the critical temperature T c , the static and dynamic critical exponents 2␤ / , , and z are obtained. The resulting values of T c are consistent with previous steady-state simulations and decrease with the increase of currents. It is found that the values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Results and discussions. -The previous short-time dynamic simulations [11,28] on the 2D FF XY model demonstrated that the finite-size effects are negligible in the clean system for L = 128. In the weakly disordered FF XY model, we have checked that the finite-size effects for L = 128 are also small enough to be neglected.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Results and discussions. -The previous short-time dynamic simulations [11,28] on the 2D FF XY model demonstrated that the finite-size effects are negligible in the clean system for L = 128. In the weakly disordered FF XY model, we have checked that the finite-size effects for L = 128 are also small enough to be neglected.…”
mentioning
confidence: 93%
“…The short-time dynamic-scaling method discovered by Janssen et al [22] has been successfully used to study the behaviors of various phase transitions [6,11,12,[23][24][25][26][27][28]. According to the short-time dynamic theory, a universal scaling form emerges in a macroscopic short-time regime of the dynamic evolution after a microscopic time scale t mic .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] More recently, this approach has been successfully extended to study the non-equilibrium phase transition with small current or field. [9] Depinning transitions are found in a large variety of physical problems, such as fluid invasion in porous media, [10,11] depinning of charge density waves, [12,13] depinning of flux line in type-II superconductors, [14−19] field-driven motion of domain walls in ferromagnets, [20,21] and elastic media in disordered environment. [22,23] In the mixed state of type-II superconductors, the magnetic field penetrates in the form of flux lines each carrying one flux quantum Φ 0 = h/2e.…”
mentioning
confidence: 99%
“…Based on the short-time dynamic scaling form, new techniques for the measurements of both dynamic and static critical exponents as well as the critical temperature have been developed [4][5][6]. Recent activities include, for example, theoretical calculations and numerical simulations of XY models and Josephson junction arrays [7][8][9][10], magnets with quenched disorder [11][12][13][14], various critical systems [15][16][17][18], and ageing phenomena [19][20][21][22][23][24]. Dynamic reweighting methods have been suggested [12,25].…”
mentioning
confidence: 99%